2015
DOI: 10.1021/jf5054589
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Dissipation of Fipronil and Its Metabolites in Peanut and Soil

Abstract: In this study, a modified quick, easy, cheap, effective, rugged, and safe (QuEChERS) method was established for the extraction and cleanup of fipronil and its three metabolites (fipronil solfone, sulfide, and desulfinyl) in peanut kernel, shell, straw, seedling, and soil samples, and liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used for analysis. The average recoveries were 66-116% at the level of 0.001-0.1 mg/kg with the RSD <19%, and the limit of detection was 0.3 ng/g for all matrices. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…GC combined with ECD, MS detectors [13, 18, 19] and LC-MS/MS [6, 20] presented a good response for fipronil and its metabolites in various matrices. However, UPLC-MS/MS provided higher sensitivity and selectivity of detection and shorter chromatography run-times than conventional GC or HPLC-MS techniques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GC combined with ECD, MS detectors [13, 18, 19] and LC-MS/MS [6, 20] presented a good response for fipronil and its metabolites in various matrices. However, UPLC-MS/MS provided higher sensitivity and selectivity of detection and shorter chromatography run-times than conventional GC or HPLC-MS techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Dutta et al [24] observed that fipronil was degraded to sulfone and desulfinyl in cabbage, and the amount of fipronil sulfone residue was greater than desulfinyl. However, Bhardwaj et al [3] and Li et al [6] studied the dissipation of fipronil on cabbage and peanut seedlings, respectively, and found that desulfinyl was the main metabolite, followed by sulfone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, various methods, like GC with electron capture detection (ECD) and MS, HPLC-MS have been reported for the analysis of fipronil and its metabolites in different matrices, such as maize [5,7], peanut [2], soil [8,9], vegetables and fruits [1,4,[10][11][12], rice [13], honey [14][15][16], pollen [17,18], sugar [6], and plasma [19,20]. However, earlier studies did not focus on development of a specific method for the analysis of fipronil and its metabolites in edible oils.…”
Section: Introductionmentioning
confidence: 99%